Agricultural rent in England, 1690-1914 - Turner, Michael Edward (Cambridge University Press, 1997)
Agricultural historians have collected and published a remarkable amount of material in recent years, partly as a result of the ongoing series 'The Agrarian History of England and Wales'. Missing from the Agrarian History volumes covering 1640–1850 has been any sustained analysis of agricultural rent, a perhaps surprising omission in view of the enormous sums of money which passed between landlords and tenants annually, and given the importance of the subject in terms of our understanding of the general course of change in agriculture and the economy more generally. In recent years the availability of estate accounts in public archive repositories has made available a range of data for the period c.1690 to the First World War, after which the material is voluminous and well known. In this book, based on research in archives across the country, the authors have produced a new rent index which will become the basis on which all future researchers in the field will rely